GABA and Neuroactive Steroid Interactions in Glia: New Roles for Old Players? - Magnaghi, Valerio (Bentham Science Publishers Ltd., 2007)
In recent years it has becoming clear that glial cells of the central and peripheral nervous system play a crucial role from the earliest stages of development throughout adult life. Glial cells are important for neuronal plasticity, axonal conduction and synaptic transmission. In this respect, glial cells are able to produce, uptake and metabolize many factors that are essential for neuronal physiology, including classic neurotransmitters and neuroactive steroids. In particular, neuroactive steroids, which are mainly synthesized by glial cells, are able to modulate some neurotransmitter receptors affecting both glia and neurons. Among the signaling systems that are specialized for neuron-glial communication, we can include neurotransmitter GABA. The main focus of this review is to illustrate the cross-talk between neurons and glial cells in terms of GABA neurotransmission and actions of neuroactive steroids. To this purpose, we will review the presence of the different GABA receptors in the glial cells of the central and peripheral nervous system. Then, we will discuss their modulation by some neuroactive steroids.